2017
DOI: 10.4103/jmas.jmas_95_16
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic splenectomy for sclerosing angiomatoid nodular transformation of the spleen

Abstract: Sclerosing angiomatoid nodular transformation (SANT) is a rare, benign, proliferative vascular lesion that arises from the splenic red pulp. Most patients with SANT have no clinical symptoms and are discovered incidentally on imaging. There are no definitive radiological signs and a distinction from other splenic diseases, and malignant processes remain difficult. Confirmation of the diagnosis of SANT requires a histological and immunohistochemical evaluation of the resected spleen. Here, we report an unusual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…SANT of the spleen is a benign disease that does not require surgery unless the patient is symptomatic. However, due to diagnostic dilemma, most patients undergo splenectomy to rule out malignancy or another pathological disease of the spleen[ 9 ]. In our case, the patient underwent laparoscopic splenectomy and recovered without complications.…”
Section: Discussionmentioning
confidence: 99%
“…SANT of the spleen is a benign disease that does not require surgery unless the patient is symptomatic. However, due to diagnostic dilemma, most patients undergo splenectomy to rule out malignancy or another pathological disease of the spleen[ 9 ]. In our case, the patient underwent laparoscopic splenectomy and recovered without complications.…”
Section: Discussionmentioning
confidence: 99%
“…The curative treatment for SANT is splenectomy [ 46 , [48] , [49] , [50] , [51] , [52] , [53] , [55] , [56] , [57] , [58] , [59] , [60] ]. Open splenectomy or minimally invasive splenectomy are both options for surgical treatment [ [62] , [63] , [64] , [65] , [66] , [67] , [68] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] ]. In recent years, minimally invasive surgery such as robotic or laparoscopic splenectomy has become more popular due to a shorter hospital stay, less postoperative abdominal pain, and an early return to normal activity [ 18 , [63] , [64] , [65] , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Open splenectomy or minimally invasive splenectomy are both options for surgical treatment [ [62] , [63] , [64] , [65] , [66] , [67] , [68] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] ]. In recent years, minimally invasive surgery such as robotic or laparoscopic splenectomy has become more popular due to a shorter hospital stay, less postoperative abdominal pain, and an early return to normal activity [ 18 , [63] , [64] , [65] , 78 ]. After total splenectomy, no evidence of recurrence was reported in the follow-up period (median follow-up:12 months (0–166)).…”
Section: Discussionmentioning
confidence: 99%
“…However, these procedure carries risks of bleeding and needle tract seeding [20]. Therefore, splenectomy may be the preferred modality to rule out malignancy or other pathological processes [24]. In addition the review of Cao et al showed that patients with SANT, indeed, have a relatively high prevalence of coexistence with diseases at other organs [17,18].…”
Section: Discussionmentioning
confidence: 99%